2017
DOI: 10.1186/s40104-017-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating leptin and its muscle gene expression in Nellore cattle with divergent feed efficiency

Abstract: BackgroundLeptin has a strong relation to important traits in animal production, such as carcass composition, feed intake, and reproduction. It is mainly produced by adipose cells and acts predominantly in the hypothalamus. In this study, circulating leptin and its gene expression in muscle were evaluated in two groups of young Nellore bulls with divergent feed efficiency. Individual dry matter intake (DMI) and average daily gain (ADG) of 98 Nellore bulls were evaluated in feedlot for 70 d to determinate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
5
11
0
6
Order By: Relevance
“…Firstly, it is important to state that the 98 animals used to select the HFE and LFE groups in this study have been previously analyzed with regard to several phenotypic and molecular measures (Alexandre et al, 2015; Mota et al, 2017; Novais et al, 2019). It was observed that HFE and LFE groups had similar body weight gain, carcass yield and loin eye area but LFE animals had higher feed intake, greater fat deposition, higher serum cholesterol levels, as well as hepatic inflammatory response, indicated by transcriptome analysis of liver biopsy and proved by the higher number of periportal mononuclear infiltrate (histopathology) and increased serum gamma-glutamyl-transferase (GGT, a biomarker of liver injury) in this group (Alexandre et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it is important to state that the 98 animals used to select the HFE and LFE groups in this study have been previously analyzed with regard to several phenotypic and molecular measures (Alexandre et al, 2015; Mota et al, 2017; Novais et al, 2019). It was observed that HFE and LFE groups had similar body weight gain, carcass yield and loin eye area but LFE animals had higher feed intake, greater fat deposition, higher serum cholesterol levels, as well as hepatic inflammatory response, indicated by transcriptome analysis of liver biopsy and proved by the higher number of periportal mononuclear infiltrate (histopathology) and increased serum gamma-glutamyl-transferase (GGT, a biomarker of liver injury) in this group (Alexandre et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that high FE animals present increased mitochondrial function (Connor et al, 2010; Lancaster et al, 2014), less oxygen consumption (Gonano et al, 2014) and delayed puberty (Shaffer et al, 2011; Randel and Welsh, 2013; Fontoura et al, 2016). On the other hand, low FE animals have increased physical activity, ingestion frequency and stress level (Kelly et al, 2010; Cafe et al, 2011; Chen et al, 2014; Francisco et al, 2015), increased leptin and cholesterol levels (Nkrumah et al, 2007; Alexandre et al, 2015; Foote et al, 2016; Mota et al, 2017), higher subcutaneous and visceral fat (Mader et al, 2009; Gomes et al, 2012; Santana et al, 2012), higher energy wastage as heat (Archer et al, 1999; Montanholi et al, 2009, 2010) and more hepatic lesions associated with inflammatory response (Alexandre et al, 2015; Paradis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On adaptation period, animals received corn silage (ad libitum), gradually replaced by trial diet (total mixed ration, including dry corn grain, corn silage, soybean, citrus pulp pellets, urea, calcareous, mineral salt and potassium chloride) offered at 8:00 h and 16:00 h. After the experiment, all animals were slaughtered following the guidelines of the Institutional Animal Care and Use Committee. More details regarding animals, diet and experimental design can be found in Alexandre et al [9] and Mota et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…As an example, for the cattle feed efficiency dataset, we found significant enrichment for genes falling in shapes 1 to 4 ( Supplementary Files 2 to 5 ), each shape capturing specific Biological Processes. The animals on the feed efficiency dataset have been already extensively characterized [ 9 , 10 , 25 , 26 , 27 , 28 ], with low feed efficiency being associated with inflammatory/immune response and altered lipid metabolism in liver. Interestingly, shape 4, the one presenting the higher number of genes and reflecting a higher number of positive correlations, is not enriched specifically for inflammatory/immune response, but for transcription-related terms, such as mRNA processing (FDR = 7.13 × 10 −19 ) and mRNA splicing (FDR = 4.54 × 10 −15 ).…”
Section: Resultsmentioning
confidence: 99%